Organic or Psychiatric Disease? A Misdiagnosed Superior Mesenteric Artery Syndrome - Rizzotto A.; Pagano B.; Giardino S. Neri F. (International Journal of Nutrition, 2016)
Superior mesenteric artery syndrome 1234 is a rare disorder characterised by a compression of the duodenum because of the reduced angle between the aorta and superior mesenteric artery. The disease is clinically characterised by abdominal pain, lack of appetite, vomiting and anorexia; some of these symptoms also characterise eating disorders. We report a case of a young female patient presenting with abdominal pain, loss of appetite and chronic loss of weight which led to misdiagnosis of anorexia nervosa; ultrasound with echo color Doppler methodology has subsequently allowed the correct diagnosis.
Keywords: weight gain